PERAN TRUST DALAM MEMEDIASI PENGARUH SOCIAL MOTIVATION TERHADAP ONLINE PURCHASE INTENTION - Tirtawati, Ida Ayu Agung; Oktora, I Gede Nandya; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
Online purchase intention is consumer behavior that shows the intention to buy a product online. Online purchase intention can be influenced by two variables, namely social motivation and trust. The purpose of this study is to explain the role of trust in mediating the effect of social motivation on online purchase intention. This study was conducted on Skintific consumers in Denpasar City by distributing questionnaires online to 110 respondents. The questionnaires instrument in this study used a Likert scale. The analysis technique used was path analysis. The result of the study showed that social motivation has a positive and significant influence on online purchase intention; social motivation has a positive and significant influence on trust; trust has a positive and significant influence on online purchase intention; and trust has a positive and significant influence in partially mediating the effect of social motivation on online purchase intention. The implications of this study are expected to provide input to Skintific to utilize aspects of social motivation and trust as a strategy to increase online purchase intention of Skintific consumers in Denpasar City.